Study and analyze the locky ransomware using malware analysis techniques - Sri Vayuputra, K; K.V.D Kiran, Dr (International Journal of Engineering and Technology, 2018)
Today most important tasks are carried in digital form this leads to increase in digital assets like laptops, smart phones, smart watches this involves in generate wide range of unique data storing in digital format like photos, voice clips, Documents, Videos, contacts etc. These all devices are connected to internet particularly laptops and smart phones. Weak security architectures always leads a chance to attackers to attack systems related to individuals, Corporates, Governments, Hospitals, Educational institutions etc. This attacks will bring huge data breaches, stealing of intellectual properties, encrypting the personal and confidential data.